Comparison of oxidative stress, lipid peroxidation and inflammatory markers between rheumatoid arthritis and ankylosing spondylitis patients - Sumbal Khan; Dr M Javad Yousaf; Dr Amir Rashid; Dr Asifa Majeed; Umer Ul Haq; Anoshia Javed (Journal of the Pakistan Medical Association, 2024)
Objective: To measure the levels of superoxide dismutase and malondialdehyde along with erythrocyte sedimentation rate and C-reactive protein in patients of rheumatoid arthritis and ankylosing spondylitis. Method: The comparative, cross-sectional study was conducted from February 2 to December 30, 2022, at the Centre for Research in Experimental and Applied Medicine laboratory of the Department of Biochemistry and Molecular Biology, Army Medical College, Rawalpindi, Pakistan, in collaboration with the Department of Rheumatology, Pak Emirates Military Hospital, Rawalpindi. The sample comprised healthy controls in group 1, patients of rheumatoid arthritis in group 2 and patients of ankylosing spondylitis in group 3. Blood samples were assessed for levels of superoxide dismutase, malondialdehyde, erythrocyte sedimentation rate and C-reactive protein. Data was analysed using SPSS 25. Results: Of the 180 subjects, 60(33.3%) were in group 1; 32(53.3%) females and 28(46.7%) males with mean age 34.9±6.4 years. There were 60(33.3%) patients in group 2; 35(58.3%) females and 25(41.7%) males with mean age 46.0±11.1 years. There were 60(33.3%) patients in group 3, and all 60(100%) were males with mean age 35.9±6.9 years. Superoxide dismutase level was significantly low and malondialdehyde level was significantly high in groups 2 and 3 compared to group 1 (p<0.05). Erythrocyte sedimentation rate was the highest in group 2, followed by group 3 (p<0.05). C-reactive protein levels were the highest in group 2 and the lowest in group 3 (p<0.05). A significantly negative correlation (p<0.001) was found between superoxide dismutase and malondialdehyde. Conclusion: Oxidative stress played a pivotal role in chronic inflammatory rheumatic diseases, like rheumatoid arthritis and ankylosing spondylitis. Key Words: Rheumatoid arthritis, Ankylosing spondylitis, Superoxide dismutase, Malondialdehyde.